Evaluation of Sucker Rod Pump Performance for Well X in the Y Field - Delfi Imelia Pitri; Samuel Roniasi Silitonga (Journal of Petroleum and Geothermal Technology, 2026)
Natural decline in reservoir pressure often causes oil wells to lose their natural flow capability, necessitating the implementation of artificial lift methods to maintain economic production levels. This study focuses on evaluating the performance of a Sucker Rod Pump (SRP) unit in Well X. Also known as beam pumping, the SRP is the oldest and most widely used artificial lift method for extracting oil from reservoirs with insufficient natural pressure. Well X exhibits a Productivity Index of 1.41 bpd/psi with a maximum flow rate of 574.082 bpd; therefore, an evaluation was conducted to determine the pump's volumetric efficiency. Currently, Well X has a total flow rate of 90 bfpd. A well is considered efficient if the volumetric efficiency of the installed pump exceeds 70%. If the efficiency falls below this threshold, optimization is required to achieve optimal performance. The evaluation results show a volumetric efficiency of 42.99%, indicating that the pump operation in this well is not yet efficient.